PEMBUATAN NEON BOX, BROSUR DAN STIKER SEBAGAI MEDIA PROMOSI PADA SANGGAR RIAS SEKAR SARI SEMARANG - Sutari Sri Rejeki; Suwardi Suwardi (Lembaga Pengembangan Kinerja Dosen, 2021)
Promotion is an important activity carried out in developing a business and business, promotion is thespearhead of the sustainability of a business itself. Lack of promotion can be an incentive for people to lookelsewhere than the place of business itself. Therefore, a special strategy is needed to advertise and inform acompany.Sekar Sari makeup studio is a service that functions personally to assist the bride and groom and theirfamilies in planning and supervising the implementation of a series of wedding events according to apredetermined schedule and budget. Therefore, to introduce or inform it, a print promotion media is neededso that all circles of society can recognize it.Based on this, the authors make print promotional media in the form of neon boxes, brochures andstickers with the aim of introducing or informing the Sekar Sari Rias Studio Semarang as a company thatprovides bridal makeup services and planning the implementation of a series of wedding events.Making designs based on existing theories and using design principles and then processing them withcomputer programs such as Adobe Photoshop CS 5.